Historical sources of institutional trajectories in economic development: China, Japan, and Korea compared - Masahiko Aoki (Asian Development Bank Institute (ADBI), 2012)
This essay provides a game-theoretic, endogenous view of institutions, and then applies the idea to identify the sources of institutional trajectories of economic development in China, Japan, and Korea. It stylizes the Malthusian-phase of East Asian economies as peasant-based economies in which small families allocated their working time between farming on small plots - leased or owned - and handcrafting for personal consumption and markets. It then compares institutional arrangements across these economies that sustained otherwise similar economies. It characterizes the varied nature of the political states of Qing China, Tokugawa Japan, and Yi Korea by focusing on the way in which agricultural taxes were enforced. It also identifies different patterns of social norms of trust that were institutional complements to, or substitutes for, political states. Finally, it traces the path-dependent transformations of these state-norm combinations along subsequent transitions to post-Malthusian phases of economic growth in the respective economies.
Keywords: O43; O53; P51; 330; china; japan; institutional complementarity; institutional change; capitalism; varieties of norms; political economy; Wirtschaftswachstum; Politisches System; Pfadabhängigkeit; Spieltheorie; Systemvergleich; China; Japan; Südkorea